Mitral Valve Disease in Thyroid Storm - Menjura, Sandra Rocio Rivera (J Endocr Soc, 2021)
Introduction: The cardiovascular effects that thyroid gland causes are widely studied. In fact, there is a known correlation between Graves’ Disease and mitral valve damage. We present the case of a patient admitted with thyroid storm and heart failure associated with severe structural damage of the mitral valve papillary muscle. Case Report: 24 year old woman with hyperthyroidism diagnosed 12 years ago, treated irregularly with thiamazole and propranolol, leaving treatment a year ago, presents dyspnea, class III functional capacity, diarrhea and logic dysphagia of a month of evolution. Heart rate over 170 bpm, respiratory rate 48 rpm and blood pressure 143/84 mmHg. Physical exam positive for exophthalmos, grade III goiter, crackles in both lung bases, pretibial myxedema and fulfilling criteria for a thyroid storm (65 points in Burch-Wartofsky Point Scale). First Lab Results: TSH<0.005µU/mL, free T4>7.7ng/dl and TRAB 37.8UI/L. Chest ray: Global cardiomegaly and pulmonary edema. EKG: Narrow complex supraventricular tachycardia. Thyroid ultrasound: Intrathoracic goiter. Transesophageal echocardiogram: Severe mitral insufficiency (Carpentier Type I and IIIB), right cavities and left ventricular enlargement, preserved right ventricular function and severe pulmonary hypertension (PSAP 71-76 mmHg). First treated with thiamazole, hydrocortisone IV, cholestyramine and sedation, falling time after into ventilatory failure and developing delirium, requiring invasive mechanical ventilation. Tested positive for COVID- 19. Starts preparation with Lugol and undergoes Total Thyroidectomy. After surgery develops severe hypocalcemia secondary to transitory hypoparathyroidism. During hospitalization presents multiple infections including pneumonia (Pseudomonas Aeruginosa), lung aspergillosis, bacteriuria (Enteroccocus Faecium) and candiduria (Candida Albicans and Glabrata), each one treated with multiple antibiotics and vasoactive drugs. Once stable, mitral valve replacement is realized, after which, the patient progresses favorably being discharged with programmed ambulatory controls. Conclusion: We report a case of a patient who was presented with positive thyroid storm criteria associated with heart failure and severe mitral valve insufficiency. The case gets complicated as multiple infections take place, including COVID-19. Fortunately, because of the early and aggressive multidisciplinary management, the patient evolved favorably, overcoming the life-threatening conditions she went through. Key Words: Thyroid storm, mitral valve insufficiency, heart failure. Bibliography: Klein I, Danzi S. Thyroid disease and the heart. Circulation. 2007 Oct 9;116(15):1725-35. doi: 10.1161/CIRCULATIONAHA.106.678326. Erratum in: Circulation. 2008 Jan 22;117(3):e18. PMID: 17923583.